Similar Positions in Classroom but Different Positions in Class: An Analysis of Narratives Based on Darvin and Norton's Investment Model - Rahele Mavaddat; Seyyed Ayatollah Razmjoo (Teaching English Language, 2020)
This study, prompted by a critical incident within the language classroom, is based on Darvin and Norton's (2015a) model of investment and an analysis of narratives of two Iranian EFL learners with different levels of investment in their language learning. The findings revealed that success in and continuity of language learning in different phases of participants' lives depended not only on their investment in language learning but also on their willingness to learn the language and motivation for it. Furthermore, emotional and temporal kinds of capital were found significant in determining participants' success or failure in language learning. Additionally, the concept of demotivation was proved inadequate for explaining one of the participants' loss of motivation for language learning over a particular period of time. Finally, a model was designed concerning the interactive effects of willingness to learn, motivation, and investment in applied linguistics.